Williams syndrome: A surprising deficit in oromotor praxis in a population with proficient language production. (January 2015) - Krishnan, Saloni; Bergström, Lina; Alcock, Katherine J.; Dick, Frederic; Karmiloff-Smith, Annette
Abstract: Williams Syndrome (WS) is a neurodevelopmental disorder of known genetic origin, characterized by serious delays in language onset yet relatively verbose, intelligible and fluent speech in late childhood and adulthood. How do motor abilities relate to language in this group? We investigated planning and co-ordination of the movement of the speech articulators (oromotor praxis) in 28 fluent-speaking individuals with WS, aged between 12 and 30 years. Results indicate that, despite their fluent language, oromotor praxis was impaired in WS relative to two groups of typically-developing children, matched on either vocabulary or visuospatial ability. These findings suggest that the ability to plan, co-ordinate and execute complex sensorimotor movements contribute to an explanation of the delay in expressive language early in development in this neurodevelopmental disorder. In the discussion, we turn to more general issues of how individual variation in oromotor praxis may account for differences in speech/language production abilities across developmental language disorders. Highlights: Individuals with Williams Syndrome are impaired when imitating oral movements. Visual presentation of movements hampers performance more than aural presentation. Initial oromotor deficits may contribute to surprising early language delays.